Effects of moderate- versus mixed-intensity training on VO2peak in young well-trained rowers - Kirchenberger, T.; Ketelhut, S.; Ketelhut, R. G. (Sports, 2021)
The effects of moderate-intensity continuous training (MICT) and a combination of MICT and high-intensity interval training (HIIT) on rowing performance and VO2peak were investigated in young athletes. Seventeen well-trained rowers (aged 15 ± 1.3 years) were randomly allocated to an intervention (IG) (n = 10) and control group (CG) (n = 7). During 8 weeks, both groups took part in the regular rowing training (3×/week MICT, 70-90 min, 65-70% of HRpeak + 2×/week resistance training). The IG completed an additional high-intensity interval training twice weekly (2 × 4 × 2 min at ˜95% of HRpeak, 60 s rest). Instead of the HIIT, the CG completed two more MICT sessions (70-90 min, 65-70% of HRpeak). Before and after the intervention, a 2000 m time trial and an exercise test were performed. The IG showed a significant improvement (p = 0.001) regarding the absolute rowing time in the graded exercise test. Furthermore, the intervention group showed a significant increase in relative VO2peak (p = 0.023), a significant increase in absolute VO2peak (p = 0.036), and a significant improvement in the 2000 m time trail (p = 0.003). No significant changes could be detected in the CG. The interaction effects were not significant. A mixed-intensity training, including HIIT, was beneficial on rowing performance and VO2peak in highly trained athletes.